2021
DOI: 10.18844/wjet.v13i2.5715
|View full text |Cite
|
Sign up to set email alerts
|

Saudi education postgraduates’ (Trainee teachers’) perspectives on distance education

Abstract: The purpose of this exploratory study undertaken in Saudi Arabia is to understand how in-service and new teachers perceive distance education. The study involved nineteen male and female postgraduates who were pursuing an education master’s degree during the COVID-19 pandemic. This is a qualitative research asking participants to provide a 300-word response to the open-ended question: “How will you implement what you have learnt in your studies so that distance education can be effectively provided and convinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…Another benefit included the opportunity to view recorded lectures later (Oyedotun, 2020). Alghamdi and Dossary (2021) also found that students reported that the experience of distance learning enhanced their skills of self-reflection, self-motivation, and self-evaluation, a finding similar to this study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Another benefit included the opportunity to view recorded lectures later (Oyedotun, 2020). Alghamdi and Dossary (2021) also found that students reported that the experience of distance learning enhanced their skills of self-reflection, self-motivation, and self-evaluation, a finding similar to this study.…”
Section: Discussionsupporting
confidence: 83%
“…This review also examines the research surrounding the experiences of higher education institutions in the Kingdom of Saudi Arabia (KSA) during the pandemic. The majority of the identified studies were surveys (Alqabbani et al, 2020;Balhareth et al, 2020;Hoq, 2020;Mukhtar & Mukhtar, 2020), with fewer qualitative studies (Alghamdi & Dossary, 2021;Khalil et al, 2020). Some studies focused on the experiences of the instructors in these institutions (Alqabbani et al, 2020;Hoq, 2020), while others focused on students' perspectives (Alghamdi & Dossary, 2021;Balhareth et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Planning for routines such as closing schools and nurseries, social distancing or confinement to the home can be a real challenge for children with physical and mental disabilities (Barlett et al, 2020). As opposed to internalising the level of anxiety that children experience with more typical painful, sad or anxious responses, acting can also occur in coercive expression behaviours such as discussion or reflection (Alghamdi & Al Dossary, 2021;Dalton et al, 2020).…”
Section: Introductionmentioning
confidence: 99%